(untitled) (American Journal of Arts and Human Science, 2023)
Standpoints on sexual issues are viewed from several angles. When acted upon, these standpoints are beneficial to the individual and others, but some results may be detrimental. Many studies have been conducted about students’ stances concerning masturbation, pornography, homosexual sex, premarital sex, and extramarital sex. Still, there is no existing study about sexual standpoints based on maritime students, even in the Philippines. This study assessed the sexual ethical perspectives of the 360 first-year maritime students of the University of Cebu for S.Y. 2020-2021. This study has used the descriptive-quantitative survey method. The frequency counts, the simple percentages, the weighted means, and the standard deviations were calculated. The questionnaire was adopted from the study. Data revealed that most respondents were uncertain whether pornography is immoral, disagreed with the idea that masturbation is immoral, agreed with the notion that homosexual sex and premarital sex are immoral, and strongly agreed on the immorality of extramarital sex. There is a correlation between gender and the respondents’ standpoints on masturbation but not pornography, homosexual sex, premarital sex, and extramarital sex. Further, there is no significant relationship between age and the respondents’ standpoints. This study will contribute to the body of knowledge in so far as it will provide facts and figures to help the government and ethics teachers of the Philippines to promote the use of books and the creation of teaching materials that include sexuality and its implications to prepare Filipino maritime students to face future sexual moral challenges.